Peptide Model of the Mutant Proinsulin Syndrome. I. Design and Clinical Correlation - Dhayalan, Balamurugan; Glidden, Michael D.; Zaykov, Alexander N.; Chen, Yen-Shan; Yang, Yanwu; Phillips, Nelson B.; Ismail-Beigi, Faramarz; Jarosinski, Mark A.; DiMarchi, Richard D.; Weiss, Michael A. (Frontiers in Endocrinology, 2022)
The mutant proinsulin syndrome is a monogenic cause of diabetes mellitus due to toxic misfolding of insulin’s biosynthetic precursor. Also designated mutant INS-gene induced diabetes of the young (MIDY), this syndrome defines molecular determinants of foldability in the endoplasmic reticulum (ER) of beta-cells. Here, we describe a peptide model of a key proinsulin folding intermediate and variants containing representative clinical mutations; the latter perturb invariant core sites in native proinsulin (LeuB15 to Pro, LeuA16 to Pro, and PheB24 to Ser). The studies exploited a 49-residue single-chain synthetic precursor (designated DesDi), previously shown to optimize in vitro efficiency of disulfide pairing. Parent and variant peptides contain a single disulfide bridge (cystine B19-A20) to provide a model of proinsulin’s first oxidative folding intermediate. The peptides were characterized by circular dichroism and redox stability in relation to effects of the mutations on (a) in vitro foldability of the corresponding insulin analogs and (b) ER stress induced in cell culture on expression of the corresponding variant proinsulins. Striking correlations were observed between peptide biophysical properties, degree of ER stress and age of diabetes onset (neonatal or adolescent). Our findings suggest that age of onset reflects the extent to which nascent structure is destabilized in proinsulin’s putative folding nucleus. We envisage that such peptide models will enable high-resolution structural studies of key folding determinants and in turn permit molecular dissection of phenotype-genotype relationships in this monogenic diabetes syndrome. Our companion study (next article in this issue) employs two-dimensional heteronuclear NMR spectroscopy to define site-specific perturbations in the variant peptides.